Disorders of circadian rhythms of heart rate variability in diabetic cardiac autonomic neuropathy: mechanisms and consequences - V.A. Serhiyenko; M.I. Dolynay; V.B. Sehin; Y.V. Lazur; A.A. Serhiyenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Abnormalities in heart rate variability (HRV) may increase the risk of cardiovascular disease over the next six years from 4 to 10 %. It is reported that the probability of stroke or cardiac death can be immediately reduced by chronobiologically assessing HRV and optimizing timed treatment efficacy. Physiological cardiovascular activities are under the control of the cardiac autonomic nervous system. Damage to the autonomic nerves results in dysfunction in heart rate control and vascular dynamics, particularly in cardiac autonomic neuropathy (CAN). Autonomic imbalance in the sympathetic (SNS) and parasympathetic nervous systems (PSNS) regulation of cardiovascular function contributes to metabolic abnormalities and significant morbidity and mortality for individuals with diabetes mellitus (DM). Misalignment of circadian rhythms has been evidenced in patients with DM, and there is a close relationship between alterations in neuroendocrine sleep architecture, circadian clock oscillations, glucose metabolism, autonomic function, and diurnal profiles of blood pressure and heart rate. Metabolic syndrome, hypertension, myocardial infarction, and DM are characterized by increased SNS activity and decreased PSNS activity. However, type 2 DM patients had a decrease in both PSNS and SNS activity. It can be explained by type 2 DM, which is a metabolic disease responsible for CAN that affects both sympathetic and parasympathetic fibers. The purpose of this review was to discuss the current state of the problem of the relationship between DM and circadian rhythm disorders, HRV. Particular attention is paid to the risk factors of diabetic CAN; insights into the mechanisms of excess mortality associated with CAN; the pathogenesis of diabetic CAN; possible pathogenic pathways binding CAN and atherosclerosis progression; genetic and epigenetic factors and CAN; DM and circadian rhythms of HRV; diabetic CAN and circadian rhythm disorders. The search was conducted in Scopus, Science Direct (from Elsevier), and PubMed, including MEDLINE databases. The keywords used were diabetes mellitus, cardiac autonomic neuropathy, circadian rhythms, heart rate variability. A manual search of the bibliography of publications was used to identify study results that could not be found during the online search.